High-safety electrolyte and lithium ion battery
By adding additives such as 2-phenyl-pyrrole derivatives and trimethyl phosphate to the electrolyte of the lithium-ion battery, a dense insulating layer is formed, which solves the safety problem of lithium-ion battery after overcharging and improves the battery's Cycle life and power performance.
Patent Information
- Application Number
- CN202411390849.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lithium-ion batteries are prone to safety problems such as collapse of electrode material structure and thermal runaway after overcharging, and anti-overcharging and flame retardant additives have a negative impact on the battery's cycle life and power performance.
A high-safety electrolyte is used, which contains lithium electrolyte, organic solvents and additives. The additives include anti-overcharge additive 2-phenyl-pyrrole derivatives and organic phosphorus-based flame retardant trimethyl phosphate. Through these additives, the additives are When the voltage exceeds 4.1V, a dense insulating layer is formed, which prevents lithium ions from moving and improves the flame retardant performance of the battery.
It effectively reduces the risk of thermal runaway after overcharging of lithium-ion batteries, while improving the cycle life and power performance of the battery, avoiding the negative impact of anti-overcharging and flame retardant additives on battery performance.
Smart Images

Figure BDA0005072372740000021 
Figure BDA0005072372740000041 
Figure BDA0005072372740000042
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a high-safety electrolyte and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are a widely used energy storage device. Compared with other chemical energy storage devices, they have higher energy density, longer cycle life, and no memory effect. Therefore, they are widely used in mobile phones, laptops, fuel vehicles, new energy vehicles, and industrial energy storage. However, when lithium-ion batteries are overcharged, the electrode material structure will collapse, the crystal form will undergo irreversible changes, and the electrolyte will continue to oxidize, eventually causing the lithium-ion battery to be scrapped, and even thermal runaway in extreme cases. Lithium-ion batteries have their own potential safety issues, which limit the further expansion of their application areas, and the safety performance requirements for lithium-ion batteries in the fields of industrial energy storage and new energy vehicles are getting higher and higher. How to improve safety performance without sacrificing the performance of lithium-ion batteries is an urgent problem to be solved in the industry.
[0003] Overcharge means that the actual charging voltage of a lithium-ion battery exceeds the upper limit voltage that the lithium-ion battery can withstand during the charging process. At present, there are many methods to prevent overcharging and flame retardancy in the industry. The method to prevent overcharging and flame retardancy in the electrolyte is to add anti-overcharge additives or flame retardant additives. Chinese patent CN116646596A discloses a method for synthesizing an anti-overcharge additive. The raw materials are propylene carbonate containing fluorine ether groups and pyridine substances, and an anti-overcharge polymer additive is synthesized. This additive can significantly improve the overcharge performance and has no effect on the battery performance. Chinese patent CN117543080A introduces two flame retardant reagents, one is a fluorocarboxylic acid ester and the other is a phosphorus-containing reagent. Fluorocarboxylic acid esters are mainly used as solvents, while phosphorus-containing reagents are mainly used as additives. After the two reagents are used in combination, the flame retardant effect of the electrolyte is significant, and the effect on the rate and cycle performance is small.
[0004] However, although the above technology improves the safety performance of lithium-ion batteries, the additional addition of anti-overcharge additives or flame retardant additives will affect the long-term cycle performance and power performance of lithium-ion batteries, resulting in a shortened life of lithium-ion batteries and reduced power performance. Summary of the invention
[0005] The object of the present invention is to provide a high-safety electrolyte that takes both cycle life and power performance into consideration; another object of the present invention is to provide a high-safety lithium-ion battery that takes both cycle life and power performance into consideration.
[0006] The present invention discloses a highly safe electrolyte, the electrolyte comprising an electrolyte lithium salt, an organic solvent and an additive, the additive comprising an anti-overcharge additive, and the anti-overcharge additive is a compound having a structure of formula (I);
[0007]
[0008] Wherein, R1 is selected from one of hydrogen, halogen, substituted or unsubstituted alkane group, olefin group, alkyne group, aromatic group, phosphate, sulfonate, sulfate, borate, siloxy, sulfite, heterocyclic group, isocyanate, cyano and silane.
[0009] In addition to the anti-overcharge additive, the additive also uses other conventional additives, such as carbon-based additives, sulfur-based additives, phosphorus-based additives, boron-based additives, nitrogen-based additives, silicon-based additives, etc. Specifically, one or more of fluorovinylene carbonate (FEC), vinyl ethylene carbonate (VEC), vinyl sulfate (DTD), 1,3-propane sultone (PS), methylene methanesulfonate (MMDS), lithium difluorobis(oxalate) phosphate (LiDFOP), lithium difluorophosphate (LiPF2O2), lithium difluorooxalate borate (LiDFOB), lithium bis(oxalate borate) (LiBOB), tris(trimethylsilyl) phosphate (TMSP), and tris(trimethylsilyl) borate (TMSB) are used.
[0010] The organic solvent is selected from one or more of carbonates, carboxylates, sulfites, phosphates, phosphites, ethers, sulfones, nitriles, and sulfites.
[0011] The organic solvent is selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, vinylene carbonate, vinyl sulfite, methyl acetate, ethyl acetate, ethyl propionate, propyl propionate, methyl propionate, propyl formate, fluorobenzene, xylene, toluene, fluoroethylene carbonate, fluoroethyl methyl carbonate, fluorodimethyl carbonate, fluorodiethyl carbonate, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, trimethyl phosphite, triethyl phosphite, tripropyl phosphite, tetrahydrofuran, acetonitrile, sulfolane, dimethyl sulfoxide, and 1,2-dimethoxyethane.
[0012] Preferably, other conventional additives are one or more of fluoroethylene carbonate (FEC), methylene methanesulfonate (MMDS), 1,3-propane sultone (PS), diethylene sulfate (DTD), tris(trimethyl)silyl phosphate (TMSP), lithium tetrafluorooxalate phosphate (LiDFOP), lithium difluorooxalate borate (LiDFOB), and lithium difluorophosphate (LiDFP).
[0013] Furthermore, the R1 is selected from one of fluorine, trimethylsilyloxy and isocyanate.
[0014] Furthermore, the amount of the anti-overcharge additive added is 1-10% of the mass of the electrolyte.
[0015] Further, the amount of the anti-overcharge additive added is 2-7% of the mass of the electrolyte. Preferably, the amount of the anti-overcharge additive added is 2-5% of the mass of the electrolyte.
[0016] Furthermore, the electrolyte also includes a flame retardant, and the flame retardant is selected from one or more of organic phosphorus flame retardants.
[0017] Adding organophosphorus flame retardants can help improve the flame retardant effect of the electrolyte after thermal runaway.
[0018] Furthermore, the flame retardant is trimethyl phosphate, and the added amount of the trimethyl phosphate accounts for 10-20% of the mass of the electrolyte.
[0019] Trimethyl phosphate will decompose at high temperatures to produce phosphorus free radicals. The phosphorus free radicals capture hydrogen free radicals in the gas, terminating the chain reaction between hydrogen free radicals and oxygen, thereby achieving a flame retardant effect.
[0020] Furthermore, the organic solvent is a combination of vinylene carbonate, vinyl sulfite and ethyl propionate.
[0021] The dielectric constant of vinyl carbonate is significantly higher than that of ethylene carbonate, and the binding ability of vinyl carbonate with lithium ions is stronger than that of ethylene carbonate with lithium ions, thereby reducing the impact of flame retardants and anti-overcharge additives and reducing damage to the interface. At the same time, the highly thermally stable interface film formed by vinyl carbonate also improves the cycle life and safety of lithium-ion batteries.
[0022] Furthermore, in the electrolyte, the amount of vinylene carbonate added is 12-18wt%, the amount of vinyl sulfite added is 3-6wt%, and the amount of ethyl propionate added is 42-50wt%.
[0023] The compatibility of trimethyl phosphate with graphite is poor, mainly because the SEI film formed by the decomposition of trimethyl phosphate is not dense, and trimethyl phosphate will enter the graphite sheet along with lithium ions, causing the peeling of graphite. The electrolyte disclosed in the present invention solves the compatibility problem of trimethyl phosphate with graphite, a negative electrode active material, by using 12-18wt% of vinylene carbonate. Since vinylene carbonate has a higher reduction potential and is easier to obtain electrons, high-content vinylene carbonate in the electrolyte preferentially obtains electrons, forming a dense interface layer, which prevents trimethyl phosphate from entering the graphite sheet along with lithium ions.
[0024] However, a high content of vinyl carbonate will bring high impedance. Once the impedance of the negative electrode interface is too large, lithium dendrites will be generated at the negative electrode interface during charging, which will eventually affect the cycle life of the lithium-ion battery. The solution to the high impedance of vinyl carbonate film formation is to add low-impedance reagents. Most low-impedance reagents will deteriorate the impedance when the content of vinyl carbonate is high, that is, these low-impedance reagents will increase the impedance of the battery. However, vinyl sulfite will not have this problem. Adding a certain amount of vinyl sulfite can significantly reduce the film formation impedance of vinyl carbonate. This is mainly because vinyl sulfite obtains an electron during the formation process to generate vinyl sulfite free radical anions, which then react with multiple vinyl carbonates to form polyvinyl carbonate-based lithium sulfite. The sulfite group of polyvinyl carbonate-based lithium sulfite has a weak ability to bind to lithium ions. The lithium ions on the SEI film composed of polyvinyl carbonate-based lithium sulfite are more likely to bind to vinyl carbonate in the solvation shell, reducing the desolvation energy of lithium ions, thereby reducing the high impedance problem caused by high content of vinyl carbonate.
[0025] Furthermore, the additives also include fluoroethylene carbonate, vinyl sulfate, and lithium difluorooxalatoborate.
[0026] Furthermore, the electrolyte lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluorosulfonyl imide), lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium perchlorate, and lithium hexafluoroarsenate.
[0027] The present invention also discloses a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and a high-safety electrolyte as described above.
[0028] The positive electrode sheet is composed of aluminum foil, positive electrode active material, conductive agent and binder.
[0029] The positive electrode active material is selected from one or more of lithium iron phosphate, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium manganese-rich oxide, lithium manganese iron phosphate, lithium cobalt oxide, and lithium nickel oxide.
[0030] The negative electrode sheet is composed of copper foil, negative electrode active material, conductive agent and binder, wherein the active material is selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon, silicon carbon and silicon oxygen.
[0031] The diaphragm is selected from one of a PP diaphragm, a PE diaphragm, a PP / PE diaphragm, a PP / PE / PP diaphragm, a ceramic diaphragm, and a rubber-coated diaphragm.
[0032] The invention provides a high-safety electrolyte, in which a small amount of an anti-overcharge additive 2-phenyl-pyrrole derivative is added to the electrolyte. The compound undergoes a polymerization reaction after the voltage exceeds 4.1V, and then forms a dense insulating polymer layer on the surface of the positive electrode, blocking the contact between the positive electrode active material and the electrolyte, cutting off the lithium ion migration path inside the battery, and reducing the risk of overcharge thermal runaway of the battery. After the 2-phenyl-pyrrole derivative is added to the electrolyte, it has a certain dehydration and acid suppression effect, and will not participate in the negative electrode film formation, and will not affect the cycle life and power performance of the lithium-ion battery. DETAILED DESCRIPTION
[0033] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.
[0034] The synthesis method of compound T1 is as follows:
[0035]
[0036] The synthesis method of compound T2 is as follows:
[0037]
[0038]
[0039] The synthesis method of compound T3 is as follows:
[0040]
[0041] Example 1
[0042] The high-safety electrolyte in this embodiment is prepared by the following steps:
[0043] Control the moisture content in the glove box to be less than 10ppm, and control the moisture content of the organic solvent to be less than 10ppm. Use a percentile balance to accurately weigh 40g of ethylene carbonate and 126g of ethyl methyl carbonate, and pour them into an aluminum bottle. After fully stirring, put it in a 0℃ constant temperature box and freeze it for 1h. Then add 27g of lithium hexafluorophosphate while stirring. Finally, add 4g of fluoroethylene carbonate, 2g of vinyl sulfate, 1g of lithium difluorooxalate borate, and 8.3g of T1 compound respectively, and stir evenly.
[0044] Inject the above electrolyte into the lithium-ion dry battery for energy storage, and then soak it in an environment of 25°C for 48 hours. After the electrolyte fully soaks the battery, start pre-charging, formation and capacity division. The pre-charging process is to charge to 10% SOC at 0.01C constant current, and then change to 30% SOC at 0.02C constant current. After pre-charging, age for 48 hours at 45°C, and then vacuum evacuate. After aging, charge to 3.65V at 0.1C constant current and constant voltage, stand for 10 minutes, and then discharge to 2.5V to determine the first charge and discharge efficiency. Next, continue aging at 45°C for 24 hours. After aging, perform capacity division. Capacity division is performed by charging to 3.65V at 0.1C constant current and constant voltage, and discharging to 2.5V at 0.1C constant current and constant voltage.
[0045] Example 2
[0046] The high-safety electrolyte in this embodiment is prepared by the following steps:
[0047] Control the moisture content in the glove box to be less than 10ppm, and control the moisture content of the organic solvent to be less than 10ppm. Use a percentile balance to accurately weigh 40g of ethylene carbonate and 126g of ethyl methyl carbonate, and pour them into an aluminum bottle. After fully stirring, put it in a 0℃ constant temperature box and freeze it for 1h. Then add 27g of lithium hexafluorophosphate while stirring. Finally, add 4g of fluoroethylene carbonate, 2g of vinyl sulfate, 1g of lithium difluorooxalate borate, and 8.3g of T2 compound respectively, and stir evenly.
[0048] Inject the above electrolyte into the lithium-ion dry battery for energy storage, and then soak it in an environment of 25°C for 48 hours. After the electrolyte fully soaks the battery, start pre-charging, formation and capacity division. The pre-charging process is to charge to 10% SOC at 0.01C constant current, and then change to 30% SOC at 0.02C constant current. After pre-charging, age for 48 hours at 45°C, and then vacuum evacuate. After aging, charge to 3.65V at 0.1C constant current and constant voltage, stand for 10 minutes, and then discharge to 2.5V to determine the first charge and discharge efficiency. Next, continue aging at 45°C for 24 hours. After aging, perform capacity division. Capacity division is performed by charging to 3.65V at 0.1C constant current and constant voltage, and discharging to 2.5V at 0.1C constant current and constant voltage.
[0049] Example 3
[0050] The high-safety electrolyte in this embodiment is prepared by the following steps:
[0051] Control the moisture content in the glove box to be less than 10ppm, and control the moisture content of the organic solvent to be less than 10ppm. Use a percentile balance to accurately weigh 40g of ethylene carbonate and 126g of ethyl methyl carbonate, and pour them into an aluminum bottle. After fully stirring, put it in a 0℃ constant temperature box and freeze it for 1h. Then add 27g of lithium hexafluorophosphate while stirring. Finally, add 4g of fluoroethylene carbonate, 2g of vinyl sulfate, 1g of lithium difluorooxalate borate, and 8.3g of T3 compound respectively, and stir evenly.
[0052] Inject the above electrolyte into the lithium-ion dry battery for energy storage, and then soak it in an environment of 25°C for 48 hours. After the electrolyte fully soaks the battery, start pre-charging, formation and capacity division. The pre-charging process is to charge to 10% SOC at 0.01C constant current, and then change to 30% SOC at 0.02C constant current. After pre-charging, age for 48 hours at 45°C, and then vacuum evacuate. After aging, charge to 3.65V at 0.1C constant current and constant voltage, stand for 10 minutes, and then discharge to 2.5V to determine the first charge and discharge efficiency. Next, continue aging at 45°C for 24 hours. After aging, perform capacity division. Capacity division is performed by charging to 3.65V at 0.1C constant current and constant voltage, and discharging to 2.5V at 0.1C constant current and constant voltage.
[0053] Example 4
[0054] The high-safety electrolyte in this embodiment is prepared by the following steps:
[0055] Control the moisture content in the glove box to be less than 10ppm, and control the moisture content of the organic solvent to be less than 10ppm. Use a percentile balance to accurately weigh 30 grams of vinyl carbonate, 12 grams of vinyl sulfite, 30 grams of trimethyl phosphate, and 96 grams of ethyl propionate, and pour them into aluminum bottles respectively. After fully stirring, put it in a 0℃ constant temperature box and freeze it for 1h. Then add 27 grams of lithium hexafluorophosphate while stirring. Finally, add 4 grams of fluoroethylene carbonate, 2 grams of vinyl sulfate, 1 gram of lithium difluorooxalate borate, and 8.3 grams of T1 compound respectively, and stir evenly.
[0056] Inject the above electrolyte into the lithium-ion dry battery for energy storage, and then soak it in an environment of 25°C for 48 hours. After the electrolyte fully soaks the battery, start pre-charging, formation and capacity division. The pre-charging process is to charge to 10% SOC at 0.01C constant current, and then change to 30% SOC at 0.02C constant current. After pre-charging, age for 48 hours at 45°C, and then vacuum evacuate. After aging, charge to 3.65V at 0.1C constant current and constant voltage, stand for 10 minutes, and then discharge to 2.5V to determine the first charge and discharge efficiency. Next, continue aging at 45°C for 24 hours. After aging, perform capacity division. Capacity division is performed by charging to 3.65V at 0.1C constant current and constant voltage, and discharging to 2.5V at 0.1C constant current and constant voltage.
[0057] Example 5
[0058] The high-safety electrolyte in this embodiment is prepared by the following steps:
[0059] Control the moisture content in the glove box to be less than 10ppm, and control the moisture content of the organic solvent to be less than 10ppm. Use a percentile balance to accurately weigh 30 grams of vinyl carbonate, 12 grams of vinyl sulfite, 30 grams of trimethyl phosphate, and 96 grams of ethyl propionate, and pour them into aluminum bottles respectively. After fully stirring, put it in a 0℃ constant temperature box and freeze it for 1h. Then add 27 grams of lithium hexafluorophosphate while stirring. Finally, add 4 grams of fluoroethylene carbonate, 2 grams of vinyl sulfate, 1 gram of lithium difluorooxalate borate, and 8.3 grams of T2 reagent respectively, and stir evenly.
[0060] Inject the above electrolyte into the lithium-ion dry battery for energy storage, and then soak it in an environment of 25°C for 48 hours. After the electrolyte fully soaks the battery, start pre-charging, formation and capacity division. The pre-charging process is to charge to 10% SOC at 0.01C constant current, and then change to 30% SOC at 0.02C constant current. After pre-charging, age for 48 hours at 45°C, and then vacuum evacuate. After aging, charge to 3.65V at 0.1C constant current and constant voltage, stand for 10 minutes, and then discharge to 2.5V to determine the first charge and discharge efficiency. Next, continue aging at 45°C for 24 hours. After aging, perform capacity division. Capacity division is performed by charging to 3.65V at 0.1C constant current and constant voltage, and discharging to 2.5V at 0.1C constant current and constant voltage.
[0061] Example 6
[0062] The high-safety electrolyte in this embodiment is prepared by the following steps:
[0063] Control the moisture content in the glove box to be less than 10ppm, and control the moisture content of the organic solvent to be less than 10ppm. Use a percentile balance to accurately weigh 30 grams of vinyl carbonate, 12 grams of vinyl sulfite, 30 grams of trimethyl phosphate, and 96 grams of ethyl propionate, and pour them into aluminum bottles respectively. After fully stirring, put it in a 0℃ constant temperature box and freeze it for 1h. Then add 27 grams of lithium hexafluorophosphate while stirring. Finally, add 4 grams of fluoroethylene carbonate, 2 grams of vinyl sulfate, 1 gram of lithium difluorooxalate borate, and 8.3 grams of T3 reagent respectively, and stir evenly.
[0064] Inject the above electrolyte into the lithium-ion dry battery for energy storage, and then soak it in an environment of 25°C for 48 hours. After the electrolyte fully soaks the battery, start pre-charging, formation and capacity division. The pre-charging process is to charge to 10% SOC at 0.01C constant current, and then change to 30% SOC at 0.02C constant current. After pre-charging, age for 48 hours at 45°C, and then vacuum evacuate. After aging, charge to 3.65V at 0.1C constant current and constant voltage, stand for 10 minutes, and then discharge to 2.5V to determine the first charge and discharge efficiency. Next, continue aging at 45°C for 24 hours. After aging, perform capacity division. Capacity division is performed by charging to 3.65V at 0.1C constant current and constant voltage, and discharging to 2.5V at 0.1C constant current and constant voltage.
[0065] Comparative Example
[0066] The electrolyte in this comparative example is prepared by the following steps:
[0067] Control the moisture content in the glove box to be less than 10ppm, and control the moisture content of the organic solvent to be less than 10ppm. Use a percentile balance to accurately weigh 40g of ethylene carbonate and 126g of ethyl methyl carbonate, and pour them into an aluminum bottle. After fully stirring, put it in a 0℃ constant temperature box and freeze it for 1h. Then add 27g of lithium hexafluorophosphate while stirring. Finally, add 4g of fluoroethylene carbonate, 2g of vinyl sulfate, and 1g of lithium difluorooxalate borate, and stir evenly.
[0068] Inject the above electrolyte into the lithium-ion dry battery for energy storage, and then soak it in an environment of 25°C for 48 hours. After the electrolyte fully soaks the battery, start pre-charging, formation and capacity division. The pre-charging process is to charge to 10% SOC at 0.01C constant current, and then change to 30% SOC at 0.02C constant current. After pre-charging, age for 48 hours at 45°C, and then vacuum evacuate. After aging, charge to 3.65V at 0.1C constant current and constant voltage, stand for 10 minutes, and then discharge to 2.5V to determine the first charge and discharge efficiency. Next, continue aging at 45°C for 24 hours. After aging, perform capacity division. Capacity division is performed by charging to 3.65V at 0.1C constant current and constant voltage, and discharging to 2.5V at 0.1C constant current and constant voltage.
[0069] Performance Test:
[0070] The electrolytes and lithium-ion batteries of Examples 1-6 and the comparative example were tested using the following method, and then a performance comparison analysis was performed.
[0071] (1) Lithium-ion battery 45°C cycle test
[0072] The lithium-ion batteries obtained in Examples 1-6 and the comparative examples were subjected to a 45°C cycle test according to the following steps. The detailed steps are as follows: Take a lithium-ion battery that has been fixed in volume, put it into a 45°C constant temperature box, and let it stand for more than 1 hour to ensure that the internal temperature of the battery is close to 45°C. Then charge it at a constant current and constant voltage of 1C, with a cut-off voltage of 3.65V and a cut-off current of 0.05C. Then discharge it to 2.5V at a constant current of 1C. Perform charge and discharge cycles on the lithium-ion battery according to the above steps, and record the discharge capacity retention rate after 1000 cycles. The discharge capacity retention rate of the battery after 1000 cycles is calculated as the discharge capacity after the cycle divided by the discharge capacity of the first cycle. See Table 1 for specific test data.
[0073] (2) Lithium-ion battery 25℃ rate test
[0074] The lithium-ion batteries obtained in Examples 1-6 and the comparative examples were tested for rate performance at 25°C according to the following steps. The lithium-ion battery was placed in a constant temperature cabinet at 25°C and allowed to stand for 6 hours before charging and discharging. First, the battery was charged at a constant current and constant voltage of 0.1C and then discharged at a constant current of 0.1C to constant capacity. Then the discharge rate was changed, and the battery was discharged to 2.5V at 0.3C, 0.5C, and 1C, respectively, to obtain the discharge capacity at different rates. The discharge capacity at different rates was divided by the discharge capacity at 0.1C to obtain the capacity retention rate at different rates. The test results of the 25°C rate are shown in Table 2.
[0075] (3) Lithium-ion battery safety testing
[0076] The lithium-ion batteries obtained in Examples 1-6 and the comparative examples were subjected to safety performance tests including overcharge tests and thermal failure tests, wherein the steps of the overcharge test are as follows: the lithium battery is charged to 3.65V at a constant current and constant voltage of 0.3C, and then charged to a cut-off voltage of up to 10V at 1C. When the current is abnormal, charging is stopped. The highest charging voltage and whether there is expansion, leakage, smoke or fire are recorded. The thermal failure test is to place the battery to be tested in the test equipment, install the charging fixture and temperature sensor, and then charge to 3.65V at a constant current of 1C. After charging to 3.65V, heating is started at a heating rate of 1.25℃ / min. When the temperature reaches the triggering condition of thermal runaway (>3℃ / second) or the temperature exceeds 300℃, heating and charging are stopped. Record the trigger temperature at which the voltage drops rapidly and whether there is expansion, leakage, smoke or fire. After testing overcharge and thermal failure, the results are listed in Table 3.
[0077] Table 1 Capacity retention test results of Examples 1-6 and Comparative Examples after 1000 cycles at 45°C
[0078]
[0079] As shown in Table 1, the data of Examples 1-6 and the comparative example show that the addition of three new anti-overcharge additives to the electrolyte system of ethylene carbonate plus ethyl methyl carbonate does not significantly deteriorate the high-temperature cycle of the battery cell, which may be related to the fact that the new additives do not participate in the negative electrode film formation, among which the T2 additive has the least effect on the high-temperature cycle. Compared with Examples 4-6, Examples 4-6 use a new organic solvent combination of vinyl carbonate, vinyl sulfite, and ethyl propionate, and the traditional organic solvent combination used in Examples 1-3. The new organic solvent combination significantly improves the cycle performance of the 45°C battery, mainly because the SEI film formed after vinyl carbonate replaces ethylene carbonate is denser and has higher thermal stability.
[0080] Table 2 Rate test results of Examples 1-6 and Comparative Examples at 25°C
[0081]
[0082] As shown in Table 2, after adding the anti-overcharge additive to the electrolyte of the comparative example in Examples 1-3, the impedance of the lithium-ion battery increased to a certain extent, among which the T2 additive had the lowest degree of deterioration of the impedance. The reason why the anti-overcharge additive deteriorates the battery impedance may be that its viscosity is relatively large, resulting in a decrease in the migration rate of lithium ions, while the additive containing siloxane groups can reduce the surface tension and increase the diffusion rate. Compared with all the examples, the degree of impedance deterioration caused by the T2 additive is relatively low. After changing the solvent system, the impedance of the battery increased slightly, mainly because the SEI membrane structure formed by vinyl carbonate is dense, and the migration resistance of lithium ions in the SEI membrane is large, resulting in a slight increase in the impedance of the new organic solvent combination. However, under the synergistic effect of vinyl sulfite, the impedance of Examples 4-6 did not increase significantly. Compared with the comparative example, the battery impedance of the lithium-ion batteries of Examples 1-6 increased less.
[0083] Table 3 Performance data results of Examples 1-6 and Comparative Examples under overcharge and thermal failure
[0084]
[0085] As shown in Table 3, compared with the comparative example, after adding the new anti-overcharge additive, the maximum voltage of Examples 1-6 is lower than 4.7V. After adding T2 or T3 additives, the upper limit voltage of the battery cannot exceed 4.5V, neither vinyl carbonate nor ethyl methyl carbonate will undergo oxidative decomposition, and the appearance of the lithium-ion battery has almost no change. After using the new organic solvent combination in Examples 4-6, since the oxidation potential of vinyl carbonate is 4.1-4.2V, the addition of T3 will cause the oxidative decomposition of vinyl carbonate, and the battery of Example 6 will swell. The polymerization voltage of T1 is higher, resulting in severe swelling in Example 4 and local leakage. From the perspective of overcharging, the performance of the T2 additive is the best. In terms of thermal failure, the addition of the new anti-overcharge additive has little effect on thermal failure, but the use of the new organic solvent combination in Examples 4-6 has significantly improved thermal failure, with the trigger temperature increased by 39°C at most, and no smoke will occur. This is mainly because the SEI film formed by vinyl carbonate has high thermal stability, and trimethyl phosphate can absorb the free radicals generated in the process, thereby inhibiting the occurrence of thermal runaway.
[0086] Combining the 45°C cycle capacity retention rate data, room temperature rate data, and safety tests, Example 5 has the most balanced performance in terms of cycle, rate, overcharge, and thermal failure.
[0087] Example 5 strengthens the interface film by changing the organic solvent combination and the film-forming body, thereby reducing this effect. Since the dielectric constant of vinylene carbonate is significantly higher than that of ethylene carbonate, the binding ability of vinylene carbonate with lithium ions is stronger than that of ethylene carbonate with lithium ions, thereby reducing the influence of flame retardant and anti-overcharge agents and reducing damage to the interface. At the same time, the interface film with high thermal stability formed by vinylene carbonate also improves the cycle life and safety of lithium-ion batteries. Through the two-aspect design of solvents and additives, the problem that the life and safety of lithium-ion batteries cannot be taken into account at the same time is solved.
[0088] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A highly safe electrolyte, characterized in that: The electrolyte comprises an electrolyte lithium salt, an organic solvent and an additive, wherein the additive comprises an anti-overcharge additive, and the anti-overcharge additive is a compound having a structure of formula (I); Wherein, R1 is selected from one of hydrogen, halogen, substituted or unsubstituted alkane group, olefin group, alkyne group, aromatic group, phosphate, sulfonate, sulfate, borate, siloxy, sulfite, heterocyclic group, isocyanate, cyano and silane.
2. A high-safety electrolyte according to claim 1, characterized in that: The R1 is selected from one of fluorine, trimethylsilyloxy and isocyanate.
3. A high-safety electrolyte according to claim 1, characterized in that: The amount of the anti-overcharge additive added is 1-10% of the mass of the electrolyte.
4. A high-safety electrolyte according to claim 1, characterized in that: The electrolyte also includes a flame retardant, and the flame retardant is selected from one or more of organic phosphorus flame retardants.
5. A high-safety electrolyte according to claim 4, characterized in that: The flame retardant is trimethyl phosphate, and the added amount of the trimethyl phosphate accounts for 10-20% of the mass of the electrolyte.
6. A high-safety electrolyte according to claim 5, characterized in that: The organic solvent is a combination of vinylene carbonate, vinyl sulfite and ethyl propionate.
7. A high-safety electrolyte according to claim 6, characterized in that: In the electrolyte, the addition amount of vinylene carbonate is 12-18wt%, the addition amount of vinyl sulfite is 3-6wt%, and the addition amount of ethyl propionate is 42-50wt%.
8. A high-safety electrolyte according to claim 1, characterized in that: The additives also include fluoroethylene carbonate, vinyl sulfate, and lithium difluorooxalate borate.
9. A high-safety electrolyte according to claim 1, characterized in that: The electrolyte lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluorosulfonyl imide), lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium perchlorate, and lithium hexafluoroarsenate.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and a high-safety electrolyte as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium battery electrolyte anti-overcharge additive and preparation method thereof
CN116646596A
Lithium ion battery electrolyte and lithium ion battery
CN117543080A
Over-charge prevention lithium ion battery electrolyte and lithium ion battery prepared by using same
CN101853963A
Lithium ion secondary battery and preparation method thereof
CN102569896A
Lithium ion battery electrolyte and lithium ion battery containing same
CN106450453A
Cited By
High-selectivity flame-retardant covalent-organic framework diaphragm as well as preparation method and application thereof
CN120033411A